Biosynthesized Carbon-derived Nanomaterials as a Photocatalytic Solution for Sustainable Water Pollution Control - Kumar, Ravi; Kaushal, Shweta; Thakur, Naveen; Kumar, Kuldeep (Nanofabrication, 2024)
Carbon nanomaterials are one of the most widely investigated nano-materials for the degradation of organic and inorganic pollutants like dyes and insecticides in an environmentally benign and that too in sustainable manner. The problems associated with the existing catalysts are related to their high band gap values and large particle sizes. In this review, the photocatalytic degradation of pollutants from industrial wastewater by using negligible amounts of carbon nanocatalysts has been covered as a solution to such types of problems. The photocatalytic activity of the carbon nanocomposites was reported to be affected by factors like particle size, nature of crystallinity, band gap, morphology and total surface area of the nanomaterials per unit mass. Despite various required optimizations, the carbon-containing nanomaterials such as carbon nanotubes, graphene, and metal oxide nanocomposites synthesized by using different methods have shown better photocatalytic activity as compared to others. This review article may open a new avenue to control water pollution efficiently and cost-effectively.